Structural relationship between borderline personality organization and thematic relationships: the mediating role of resistibility in young boys and girls - Naseh Jahaghi, Faezeh; Mirzahoseini, Hassan; Monirpoor, Nader (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to explain the organization of border personality based on the initial thematic relationships and resilience. Methods: This descriptive study was performed by correlation method. The statistical population included all undergraduate and graduate students of Tehran universities in the academic year 1401-1400, of which 412 were selected using the available sampling method. Participants completed the Bell et al. (1985) Thematic Relationships Questionnaire, the Kernberg Borderline Personality Organization (2002), and the Ashourpour et al. (2010) Resilience Scale. Structural equation modeling was performed using the data obtained from the questionnaires. Results: The results showed that thematic relationships directly explain 0.29% and due to resilience 0.19% of the borderline personality structure. Overall, the estimation of the structural model in which the thematic relations of the predictor variable and resilience were entered as mediating variables, showed that this model explains 0.19% of the borderline personality structure (P